(3EQTGO GdhdO ajeG jLH dcd CMOs - (3eMeO YGbd Hf eMeO cGTa GdHNGQj GdMfajs ((3eMehO GdYdGa s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdeYGd CYde CjgG GdhdO GdfHjd, hGdfLd GdSdjd Cf GdhdO CHhPcQ CHjg HYO ahJg, heMji CSeg HYO ehJg, heWeM fXQ GdQLd hdO jbhe ebGeg s
(3BNQgG (B:s
(3hGYQa Mb faSc hYGTQ CHfGA LfSc gOGc Gddg dCbhe WQjb s
(3GdeNWhW HBNQg JbQjXGJs
(3GfXQ GdLRA GdChd HQbe (B23 (3COHs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B21 s
Keywords: (3GdCOHs